Theory Versus Practice in Risk Analysis: An Empirical Study. - Greer, Willis R. (The Accounting Review, 1974)
This article presents a study on the theory versus practice in risk analysis in decision making in the U.S. There appears to be substantial conflict between the decision processes used by actual decision makers and existing utility theory. The conflict seems to center around the inability of classical utility theory to deal effectively with situations where one or more contingent outcomes for a project are lower than some critical amount. Existing theory, therefore, incorrectly models practice. Contributing factors in the apparent conflict may be internal inconsistency and a tendency decision makers have to be more averse to risk at the time of actual choice than their pre-decision statements would indicate.